First Italian Consensus Conference on VATS Lobectomy for NSCLC. Issue 2 (March 2017) - Nosotti, Mario; Droghetti, Andrea; Luzzi, Luca; Solli, Piergiorgio; Crisci, Roberto
Purpose: Video-assisted thoracoscopic surgery (VATS) lobectomy has become an accepted procedure for the treatment of selected cases of lung cancer. The aim of this project was to establish national practical recommendations for the management of patients suitable for VATS lobectomy. Methods: The Scientific Committee of the VATS Lobectomy Group (a branch of the Italian Society of Thoracic Surgery) identified the consensus conference as an appropriate tool for a national debate. The consensus conference was organized following indications of the Italian Department of Health: a panel of experts reviewed the literature, the jury board revised the experts' reports, and the national conference discussed and voted on statements. The strength of recommendation for a statement was classified as weak, fair, or high when the total score ranged between 51% and 67%, 68% and 84%, or 85% and 100%, respectively. Results: Eighty-six Italian thoracic surgeons attended the 1 st Italian Consensus Conference on VATS lobectomy in Giulianova, Italy, on October 29-30, 2015. Thirty-three topics were discussed: indications, surgical strategy, perioperative management, and training were the main topics. Consensus was reached on 24 statements that were consequently recommended. Conclusions: The Italian Consensus Conference is the first attempt to discuss VATS lobectomy-related issues in a national scientific community. Such experience determined an improvement in epistemic knowledge among the Italian thoracic surgeons and could be a suggestion for other national communities.